Preparation method of resin composition, resin composition and application thereof

By adjusting the addition order of inorganic fillers and combining the use of high thermal conductivity and high Dk inorganic substances, the problem of uneven dispersion of inorganic fillers in the prior art is solved, and a resin combination of high thermal conductivity, high dielectric constant and low dielectric loss is realized Things.

CN119391131APending Publication Date: 2025-02-07SHENGYI TECH (CHANGSHU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411505224.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

While improving the thermal conductivity and dielectric constant of electronic circuit substrates, it is difficult to effectively disperse inorganic fillers, resulting in a decrease in thermal conductivity and Dk value, and there are problems of coagulation and settlement.

Method used

By adjusting the order of addition of nitrogen inorganic substances and titanate inorganic substances, first add nitrogen inorganic substances, then add titanate inorganic substances, and use high thermal conductivity of nitrogen inorganic substances and high Dk titanate substances. Inorganic substances and reduce dielectric loss through active esters and cyanate ester compounds, thereby improving heat resistance.

Benefits of technology

Good dispersion of inorganic filler is achieved, the thermal conductivity and dielectric constant of the resin composition are improved, the dielectric loss is reduced, and cured substances with high heat resistance, high thermal conductivity, high dielectric constant and low dielectric loss are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391131A_ABST
    Figure CN119391131A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a resin composition, the resin composition and application of the resin composition. The preparation method of the resin composition comprises the following steps: S1, uniformly stirring 10-60 parts by weight of a cyanate ester compound, 10-80 parts by weight of epoxy resin, 5-60 parts by weight of active ester and 10-200 parts by weight of an organic solvent to obtain a resin glue solution; s2, firstly adding 5-100 parts by weight of nitrogen inorganic matters or dispersion liquid thereof into the resin glue solution, and uniformly stirring; s3, adding 30-100 parts by weight of titanate inorganic matter or dispersion liquid of the titanate inorganic matter, and uniformly stirring to obtain a resin composition; wherein the nitrogen inorganic matter is selected from at least one of aluminum nitride, boron nitride or silicon nitride; the titanate inorganic matter is selected from at least one of calcium titanate, strontium titanate, barium titanate, lead titanate, magnesium titanate, lead zirconate titanate and lead lanthanum zirconate titanate; and a cured product with high heat resistance, high thermal conductivity, high dielectric constant and low dielectric loss is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic materials, and in particular to a preparation method of a resin composition, the resin composition and applications thereof. Background Art

[0002] This year, the trend of high-power electronic components, ultra-thin circuit boards and high-density assembly of complete machines has become increasingly obvious, which has put forward higher requirements on the heat dissipation of electronic circuit substrates. At the same time, with the rapid development of modern communication technology, the operating frequency of electronic equipment is getting higher and higher, and the heat generation is getting higher and higher. If the accumulated heat cannot be discharged in time, the operating temperature of the equipment will increase. In the long run, it will cause the electrical performance of the components to decline or even be damaged, seriously damaging the life and reliability of the equipment. In order to improve the thermal conductivity, aluminum substrates or a large amount of inorganic fillers are used in the prior art, but the dispersion of inorganic fillers in the resin glue is limited. When the content is higher than a certain range, it is easy to produce problems of uneven dispersion such as coagulation and sedimentation.

[0003] On the other hand, radio navigation is developing rapidly and the mobile communication market is becoming increasingly open, which has led to the rapid development of various positioning and navigation systems, such as vehicle positioning, communication positioning, remote control mapping, and electronic navigation, and has been continuously miniaturized. However, the size of the RF front-end device is inversely proportional to the dielectric constant of the substrate, so the development of high dielectric constant substrates is imperative. At the same time, the fields of high-frequency communication equipment, frequency converters, and piezoelectric sensors are developing rapidly, and the demand for high dielectric constant substrates is increasing, and the development of high dielectric constant substrates is highly anticipated. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a resin composition, the resin composition and application thereof.

[0005] To achieve the above-mentioned object of the invention, the present invention adopts the following technical scheme: a method for preparing a resin composition, comprising the following steps:

[0006] S1: 10-60 parts by weight of a cyanate compound, 10-80 parts by weight of an epoxy resin, 5-60 parts by weight of an active ester and 10-200 parts by weight of an organic solvent are stirred uniformly to obtain a resin glue solution;

[0007] S2: first add 5-100 parts by weight of nitrogen-based inorganic substances or their dispersions into the resin glue and stir evenly;

[0008] S3: adding 30-100 parts by weight of a titanate inorganic substance or a dispersion thereof, stirring evenly to obtain a resin composition;

[0009] Among them, the nitrogen-based inorganic substance is selected from at least one of aluminum nitride, boron nitride or silicon nitride; the titanate-based inorganic substance is selected from at least one of calcium titanate, strontium titanate, barium titanate, lead titanate, magnesium titanate, lead zirconate titanate, and lead lanthanum zirconate titanate.

[0010] As a further improvement of the present invention, the average particle size of the nitrogen-based inorganic material is 3-25 μm; the average particle size of the titanate-based inorganic material is 0.1-5 μm.

[0011] As a further improvement of the present invention, the viscosity of the resin glue obtained in step S1 at room temperature is 50-350 Pa·s.

[0012] As a further improvement of the present invention, the viscosity of the resin glue obtained in step S2 at room temperature is 200-600 Pa·s.

[0013] As a further improvement of the present invention, the organic solvent in the dispersion is of the same type as the organic solvent in step S1.

[0014] As a further improvement of the present invention, the active ester contains the following structure:

[0015] Ar is C6-C 20 Arylene, Ar' is C1-C 20 An alkyl, aryl or alicyclic group.

[0016] As a further improvement of the present invention, Ar' is naphthyl, dicyclopentadienyl or Or -O-; wherein Ar is phenyl.

[0017] As a further improvement of the present invention, 0.05-5 parts by weight of a curing accelerator is also added in step S1.

[0018] To achieve the above object of the invention, the present invention further provides a resin composition, which is prepared by the above method for preparing the resin composition.

[0019] To achieve the above-mentioned object of the invention, the present invention also provides a use of the above-mentioned resin composition in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.

[0020] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0021] In the preparation method of the resin composition of the present invention, on the one hand, by adjusting the order of adding two inorganic fillers, nitrogen-based inorganic fillers are added first, and then titanate-based inorganic fillers are added, so that the two inorganic fillers with higher density can be well dispersed in the resin system, the dispersion performance of the inorganic fillers is improved, and the decrease of thermal conductivity and Dk value is suppressed; on the other hand, by using nitrogen-based inorganics with high thermal conductivity in combination with titanate-based inorganics with high Dk (dielectric constant), the thermal conductivity and Dk value of the resin composition are further improved, and at the same time, active esters and cyanate compounds are used to further reduce dielectric loss and improve heat resistance. On the basis of obtaining a resin composition that meets high heat resistance and low dielectric loss, the thermal conductivity and high dielectric constant of the resin composition are improved, and good resin filler wettability is ensured, so as to obtain a cured product with high heat resistance, high thermal conductivity, high dielectric constant and low dielectric loss, thereby obtaining a cured product with excellent comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a flow chart of a method for preparing a resin composition in a specific embodiment of the present invention. DETAILED DESCRIPTION

[0023] The following is a specific implementation of the embodiment of the present invention. It should be pointed out that for ordinary technicians in this field, several improvements and modifications can be made without departing from the principles of the embodiment of the present invention. These improvements and modifications are also considered to be within the scope of protection of the embodiment of the present invention.

[0024] The terms “comprising” and “containing” in the present specification mean that other components may be contained in addition to the components mentioned above, and these other components can impart different characteristics to the resin composition.

[0025] Combination Figure 1 As shown, the present invention provides a method for preparing a resin composition, comprising the following steps:

[0026] S1: 10-60 parts by weight of a cyanate compound, 10-80 parts by weight of an epoxy resin, 5-60 parts by weight of an active ester and 10-200 parts by weight of an organic solvent are stirred uniformly to obtain a resin glue solution;

[0027] S2: first add 5-100 parts by weight of nitrogen-based inorganic substances or their dispersions into the resin glue and stir evenly;

[0028] S3: adding 30-100 parts by weight of a titanate inorganic substance or a dispersion thereof, stirring evenly to obtain a resin composition;

[0029] Among them, the nitrogen-based inorganic substance is selected from at least one of aluminum nitride, boron nitride or silicon nitride; the titanate-based inorganic substance is selected from at least one of calcium titanate, strontium titanate, barium titanate, lead titanate, magnesium titanate, lead zirconate titanate, and lead lanthanum zirconate titanate.

[0030] In the preparation method of the resin composition of the present invention, on the one hand, by adjusting the order of adding two inorganic fillers, nitrogen-based inorganic fillers are added first, and then titanate-based inorganic fillers are added, so that the two inorganic fillers with higher density can be well dispersed in the resin system, the dispersion performance of the inorganic fillers is improved, and the decrease of thermal conductivity and Dk value is suppressed; on the other hand, by using nitrogen-based inorganics with high thermal conductivity in combination with titanate-based inorganics with high Dk (dielectric constant), the thermal conductivity and Dk value of the resin composition are further improved, and at the same time, active esters and cyanate compounds are used to further reduce dielectric loss and improve heat resistance. On the basis of obtaining a resin composition that meets high heat resistance and low dielectric loss, the thermal conductivity and high dielectric constant of the resin composition are improved, and good resin filler wettability is ensured, so as to obtain a cured product with high heat resistance, high thermal conductivity, high dielectric constant and low dielectric loss, thereby obtaining a cured product with excellent comprehensive performance.

[0031] It should be noted that the cured product in the present invention can be understood as a prepreg, an insulating film, an insulating board, a copper-clad laminate, a circuit substrate, an electronic device, and the like.

[0032] In some optional embodiments, the viscosity of the resin glue obtained in step S1 at room temperature is 50-350Pa·s, such as 50Pa·s, 100Pa·s, 150Pa·s, 200Pa·s, 250Pa·s, 300Pa·s, 350Pa·s and any point value between the above points, which will not be repeated here. When the viscosity of the resin glue obtained in step S1 at room temperature is lower than 50Pa·s, the nitrogen inorganic substance in step S2 can be dispersed more evenly in the resin glue, but it is easy to settle; when the viscosity of the resin glue obtained in step S1 at room temperature is higher than 350Pa·s, the nitrogen inorganic substance in step S2 is not easy to disperse evenly in the resin glue and is easy to agglomerate. Therefore, in the present invention, the viscosity of the resin glue obtained in step S1 at room temperature is controlled to be 50-350 Pa·s, so that the nitrogen-based inorganic substances in step S2 can be well dispersed in the resin glue without agglomeration and sedimentation, thereby improving the thermal conductivity of the final resin composition.

[0033] In a specific embodiment, the viscosity of the resin glue obtained in step S1 at room temperature is 100-230 Pa·s, such as 100 Pa·s, 120 Pa·s, 140 Pa·s, 160 Pa·s, 180 Pa·s, 200 Pa·s, 230 Pa·s and any point value between the above points, which will not be repeated here.

[0034] In some optional embodiments, the viscosity of the resin glue obtained in step S2 at room temperature is 200-600Pa·s, such as 200Pa·s, 250Pa·s, 300Pa·s, 350Pa·s, 400Pa·s, 450Pa·s, 500Pa·s, 550Pa·s, 600Pa·s and any point value between the above point values, which will not be repeated here. When the viscosity of the resin glue obtained in step S2 at room temperature is lower than 200Pa·s, the titanate inorganic substance in step S3 can be dispersed more evenly in the resin glue, but it is easy to settle; when the viscosity of the resin glue obtained in step S2 at room temperature is higher than 600Pa·s, the titanate inorganic substance in step S3 is not easy to disperse evenly in the resin glue and is easy to agglomerate. Therefore, in the present invention, the viscosity of the resin glue obtained in step S2 at room temperature is controlled to be 200-600 Pa·s, so that the titanate inorganic substance in step S3 can be well dispersed in the resin glue without agglomeration and sedimentation, thereby inhibiting the decrease in the Dk value of the resin composition.

[0035] In a specific embodiment, the viscosity of the resin glue obtained in step S2 at room temperature is 260-500 Pa·s, such as 260 Pa·s, 280 Pa·s, 300 Pa·s, 320 Pa·s, 340 Pa·s, 360 Pa·s, 380 Pa·s, 500 Pa·s and any point value between the above points, which will not be repeated here.

[0036] Specifically, the organic solvent in step S1 is selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene, and cyclohexane.

[0037] When the dispersion of the corresponding inorganic filler is added in step S2 and / or step S3, the dispersion includes an inorganic substance, a coupling agent and an organic solvent. For example, the dispersion of the nitrogen inorganic substance in step S2 includes a nitrogen inorganic substance, a coupling agent and an organic solvent; the dispersion of the titanate inorganic substance in step S3 includes a titanate inorganic substance, a coupling agent and an organic solvent.

[0038] In a preferred embodiment, the organic solvent in the dispersion is of the same type as the organic solvent in step S1, which can improve the mixing performance of the dispersion and the resin glue in step S1, thereby further improving the dispersibility of each inorganic filler.

[0039] Specifically, the coupling agent in the dispersion is a silane coupling agent, specifically at least one of epoxy silane coupling agent, amino silane coupling agent, vinyl silane coupling agent, methacrylate silane coupling agent or mercapto silane coupling agent, which can improve the dispersibility of the corresponding inorganic filler.

[0040] In some optional embodiments, the average particle size of the nitrogen inorganic material is 3-25 μm; the average particle size of the titanate inorganic material is 0.1-5 μm. When a nitrogen inorganic filler with a large particle size and a titanate inorganic filler with a small particle size are used in combination, the small particle size titanate inorganic filler will be dispersed into the nitrogen inorganic filler with a large particle size, which not only increases the filling amount of the filler, but also maximizes the packing density of the filler, forms a conductive path and improves the dispersion of the filler, while suppressing the decrease of the dielectric constant, thereby obtaining a solidified material with both high thermal conductivity and high dielectric constant.

[0041] In a specific embodiment, the average particle size of the nitrogen-based inorganic substance can be selected to be 6-15 μm, such as 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 15 μm and specific point values ​​between the above values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0042] Specifically, the nitrogen-based inorganic material is SP3-7 or SGP manufactured by DENKA, FAN-f30 or FAN-f-50 manufactured by Furukawa Electronics, HP-40, HP-40MF or HP40-J2 manufactured by Mizushima Alloy, MBN-010T manufactured by Mitsui Chemicals, and SN-1040 manufactured by Lianrui New Materials.

[0043] In a specific embodiment, the average particle size of the titanate inorganic material is 0.5-3 μm, such as 0.5 μm, 0.8 μm, 1.1 μm, 1.4 μm, 1.7 μm, 3 μm and specific point values ​​between the above values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0044] For example, the titanate inorganic material is selected from CT-3, ST-2, SBT-K3 or BT-HP9DX manufactured by Kyoritsu Materials, SW-100, SW-50C, SW-100C, SW-200C, SW-320C or SW-350 manufactured by Titanium Industries, and ST, ST-S1, HST-1, HPST-1 or HPST-2 manufactured by Fuji Titanium Industries.

[0045] In some optional embodiments, the active ester contains the following structure:

[0046] Among them, Ar is C6-C 20 Arylene, Ar' is C1-C 20 An alkyl, aryl or alicyclic group.

[0047] In one embodiment, Ar' is naphthyl, dicyclopentadienyl or Or -O-; wherein Ar is phenyl.

[0048] Specifically, the active ester is selected from HPC-8000 series manufactured by DIC, V-575 or V-577 manufactured by UNITIKA.

[0049] In some optional embodiments, the epoxy resin in step S1 is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, naphthalene-type epoxy resin, phosphorus-containing epoxy resin, o-cresol epoxy resin, bisphenol A novolac epoxy resin, phenol novolac epoxy resin, trifunctional phenol-type epoxy resin, tetraphenylethane epoxy resin, biphenyl-type epoxy resin, dicyclopentadiene-type epoxy resin, isocyanate-type epoxy resin, aralkyl linear novolac epoxy resin, alicyclic epoxy resin, glycidylamine-type epoxy resin, and glycidylester-type epoxy resin.

[0050] Specifically, the epoxy resin is selected from HP4032, HP4032H, HP4032D, HP4032SS, HP4700, HP4710, N-690, N-695, HP7200, HP7200H, HP7200HH, EXA7311, HP6000 manufactured by DIC, NC3000, NC7000, NC3100 manufactured by Nippon Kayaku, and ESN475V, ESN485 manufactured by Nippon Steel Chemical.

[0051] In some optional embodiments, the cyanate compound contains at least one of the following structures:

[0052]

[0053]

[0054] The number n of repeating units in the structural formulae (1) to (6) is an integer of 1 to 10.

[0055] Specifically, the cyanate compound may be a monomer, a polymer, a prepolymer, or a combination of any two.

[0056] In some optional embodiments, 0.05-5 parts by weight of a curing accelerator is further added in step S1.

[0057] Specifically, the curing accelerator is at least one of 2-methylimidazole, undecylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 1-cyanoethyl substituted imidazole, benzyldimethylamine, cobalt acetylacetonate, copper acetylacetonate or zinc isooctanoate.

[0058] In some optional embodiments, the method for preparing the resin composition further includes the following step: in step S1, 5-60 parts by weight of a flame retardant is added to the resin glue solution, so that the final resin composition has flame retardant properties.

[0059] The flame retardant is selected from at least one of a bromine flame retardant, a phosphorus flame retardant, a nitrogen flame retardant, an organic silicon flame retardant, and an organic metal salt flame retardant.

[0060] Specifically, the bromine flame retardant is selected from decabromodiphenyl ether, decabromodiphenyl ethane, brominated styrene or tetrabromophthalamide; the phosphorus flame retardant is selected from inorganic phosphorus, condensed phosphate ester, phosphoric acid, hypophosphite, phosphorus oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, (k is an integer from 1 to 5), 10-phenyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2,6-dimethylphenyl)phosphine, phosphazene, modified phosphazene.

[0061] In a preferred embodiment, the flame retardant is a condensed phosphate ester, a hypophosphite or a bis-DOPO compound.

[0062] Furthermore, the present invention also provides a resin composition prepared by the above-mentioned method for preparing the resin composition.

[0063] Furthermore, the present invention also provides a use of the above resin composition in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.

[0064] Specifically, the present invention further provides a prepreg, which comprises a reinforcing material and the above-mentioned resin composition, wherein the resin composition is impregnated on the reinforcing material.

[0065] The reinforcing material may be selected from at least one of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fabrics.

[0066] Preferably, the reinforcing material is glass fiber cloth. Among the glass fiber cloth, open fiber cloth or flat cloth is preferably used. More preferably, the glass fiber cloth is E glass fiber cloth, S glass fiber cloth, T glass fiber cloth or Q glass fiber cloth.

[0067] In addition, when the reinforcing material is glass fiber cloth, the glass fiber cloth generally needs to be chemically treated to improve the interface bonding between the resin composition and the glass fiber cloth. The main method of the chemical treatment is coupling agent treatment, and the coupling agent used is preferably epoxy silane coupling agent or amino silane coupling agent, so that the reinforcing material has good water resistance and heat resistance.

[0068] Specifically, the method for preparing the prepreg comprises the following steps:

[0069] The reinforcing material is immersed in the above-mentioned resin composition, and then the immersed reinforcing material is taken out and heated and dried to obtain the prepreg. It is known that the resin composition prepared by the above-mentioned method for preparing the resin composition is in a glue liquid state.

[0070] In a specific embodiment, the impregnated reinforcing material is baked at 100° C. to 180° C. for 1 min to 15 min, and the prepreg is obtained after drying.

[0071] In the present invention, the viscosity of the glue solution of the resin composition used in preparing the prepreg is not specifically limited, as long as the glue solution of the resin composition reaches a viscosity suitable for use.

[0072] The present invention also provides a copper-clad laminate, which comprises at least one of the above-mentioned prepregs and a metal foil formed on at least one side of the prepreg. When the copper-clad laminate comprises only one of the above-mentioned prepregs, the metal foil is arranged on at least one side of the surface of the prepreg. When the copper-clad laminate comprises at least two of the above-mentioned prepregs, the at least two prepregs are stacked and bonded together by heating and pressurizing to form a combined sheet, and then the metal foil is bonded on one side or both sides of the combined sheet by heating and pressurizing to form the copper-clad laminate.

[0073] Specifically, the preparation steps of the copper-clad laminate are as follows: a single side or double sides of a prepreg is coated with metal foil, or at least two prepregs are stacked to form a combined sheet, a single side or double sides of the combined sheet is coated with metal foil, and hot pressing is performed to obtain a copper-clad laminate.

[0074] The pressing conditions of the copper-clad laminate are: pressing at a pressure of 0.2 to 2 MPa and a temperature of 150° C. to 250° C. for 1 to 4 hours.

[0075] Specifically, the number of the prepregs can be determined according to the required thickness of the copper-clad laminate, and one or more prepregs can be used.

[0076] The metal foil may be copper foil or aluminum foil, and its material is not limited; the thickness of the metal foil is not particularly limited, such as 5 μm, 8 μm, 12 μm, 18 μm, 35 μm or 70 μm.

[0077] The present invention also provides an insulating plate, which comprises at least one of the aforementioned prepreg sheets.

[0078] The present invention also provides an insulating film, which comprises a carrier film and the aforementioned resin composition coated thereon, and can significantly improve the heat resistance of the insulating film.

[0079] The preparation method of the insulating film is as follows: coating a glue liquid of the resin composition on a carrier film, and heating and drying the carrier film coated with the glue liquid of the resin composition to obtain the insulating film.

[0080] In a specific embodiment, the carrier film coated with the resin composition glue is baked at 100° C. to 160° C. for 3 min to 10 min, and the insulating film can be obtained after drying.

[0081] The solvent is selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene and cyclohexane.

[0082] The carrier film is selected from at least one of PET film, PP film, PE film and PVC film.

[0083] The present invention also provides a circuit substrate, which includes one or more of the aforementioned prepreg, copper-clad laminate, insulating plate, and insulating film.

[0084] The present invention also provides an electronic device, which includes the aforementioned circuit substrate.

[0085] The content of the present invention will be described in detail below with reference to the preparation method of the resin composition corresponding to the specific embodiments; of course, it can be understood that the embodiments of the present invention are not limited to these embodiments.

[0086] Examples 1 to 4 and Comparative Examples 1 to 4:

[0087] Embodiment 1:

[0088] A method for preparing a resin composition comprises the following steps:

[0089] S1: 40 parts by weight of bisphenol A cyanate prepolymer (produced by Tianqi), 60 parts by weight of biphenyl epoxy resin (NC3000 produced by Huayao), 20 parts by weight of dicyclopentadiene active ester (produced by DIC, HPC-8000), 0.5 parts by weight of 2-methylimidazole and 100 parts by weight of butanone were stirred uniformly to obtain a resin glue having a viscosity of 157 Pa·s;

[0090] S2: First, add 70 parts by weight of boron nitride (made of water island alloy, HP40-J2, D50 = 16.0 μm) to the above resin glue, continue to stir evenly, and obtain a resin glue with a viscosity of 320 Pa.s;

[0091] S3: adding 50 parts by weight of calcium titanate (manufactured by Kyoritsu Materials, D50=2.0 μm) and stirring evenly to obtain a resin composition corresponding to Example 1;

[0092] The viscosity in steps S1, S2 and S3 is measured by a rotational viscometer at room temperature.

[0093] Example 2

[0094] A method for preparing a resin composition comprises the following steps:

[0095] S1: 40 parts by weight of bisphenol A cyanate prepolymer (produced by Tianqi), 60 parts by weight of biphenyl epoxy resin (NC3000 produced by Huayao), 20 parts by weight of dicyclopentadiene active ester (produced by DIC, HPC-8000), 0.5 parts by weight of 2-methylimidazole and 100 parts by weight of butanone were stirred uniformly to obtain a resin glue having a viscosity of 157 Pa·s;

[0096] S2: Add 50 parts by weight of boron nitride (made of Mizushima alloy, HP40-J2, D50=16.0 μm) to the above resin glue, continue to stir evenly, and obtain a resin glue with a viscosity of 281 Pa.s;

[0097] S3: Continue to add 70 parts by weight of calcium titanate (made by Kyoritsu Materials, D50=2.0 μm), and stir evenly to obtain a resin composition corresponding to Example 2;

[0098] The viscosity in steps S1, S2 and S3 is measured by a rotational viscometer at room temperature.

[0099] Example 3

[0100] A method for preparing a resin composition comprises the following steps:

[0101] S1: 40 parts by weight of bisphenol A cyanate prepolymer (produced by Tianqi), 60 parts by weight of biphenyl epoxy resin (NC3000 produced by Huayao), 20 parts by weight of dicyclopentadiene active ester (produced by DIC, HPC-8000), 0.5 parts by weight of 2-methylimidazole and 100 parts by weight of butanone were stirred uniformly to obtain a resin glue having a viscosity of 157 Pa·s;

[0102] S2: Add 50 parts by weight of silicon nitride (produced by Lianrui, D50=6.0 μm) to the above resin glue, continue to stir evenly, and obtain a resin glue with a viscosity of 296 Pa.s;

[0103] S3: Continue to add 70 parts by weight of strontium titanate (produced by Sakai Chemical Industry, ST-03, D50=0.3 μm), and stir evenly to obtain a resin composition corresponding to Example 3;

[0104] The viscosity in steps S1, S2 and S3 is measured by a rotational viscometer at room temperature.

[0105] Example 4

[0106] A method for preparing a resin composition comprises the following steps:

[0107] S1: 30 parts by weight of phenolic cyanate prepolymer (produced by Tianqi), 80 parts by weight of biphenyl epoxy resin (NC3000 produced by Huayao), 35 parts by weight of dicyclopentadiene active ester (produced by DIC, HPC-8000), 0.5 parts by weight of 2-methylimidazole and 50 parts by weight of butanone were stirred uniformly to obtain a resin glue with a viscosity of 203 Pa·s;

[0108] S2: Add 80 parts by weight of silicon nitride (produced by Lianrui, D50=6.0 μm) to the above resin glue, continue to stir evenly, and obtain a resin glue with a viscosity of 423 Pa.s;

[0109] S3: Continue to add 70 parts by weight of strontium titanate (produced by Sakai Chemical Industry, ST-03, D50=0.3 μm), and stir evenly to obtain a resin composition corresponding to Example 4;

[0110] The viscosity in steps S1, S2 and S3 is measured by a rotational viscometer at room temperature.

[0111] Comparative Example 1

[0112] A method for preparing a resin composition comprises the following steps:

[0113] S1: 40 parts by weight of bisphenol A cyanate prepolymer (produced by Tianqi), 60 parts by weight of biphenyl epoxy resin (NC3000 produced by Huayao), 20 parts by weight of dicyclopentadiene active ester (produced by DIC, HPC-8000), 0.5 parts by weight of 2-methylimidazole and 5 parts by weight of butanone were stirred uniformly to obtain a resin glue with a viscosity of 308 Pa·s;

[0114] S2: Add 70 parts by weight of boron nitride (manufactured by DENKA, D50=2.0 μm) to the above resin glue solution, continue stirring to obtain a resin glue solution with a viscosity of 611 Pa.s;

[0115] S3: Continue to add 50 parts by weight of calcium titanate (made by Kyoritsu Materials, D50=2.0 μm), and stir evenly to obtain a resin composition corresponding to Comparative Example 1;

[0116] The viscosity in steps S1, S2 and S3 is measured by a rotational viscometer at room temperature.

[0117] Comparative Example 2

[0118] A method for preparing a resin composition comprises the following steps:

[0119] S1: 40 parts by weight of bisphenol A cyanate prepolymer (produced by Tianqi), 60 parts by weight of biphenyl epoxy resin (NC3000 produced by Huayao), 20 parts by weight of dicyclopentadiene active ester (produced by DIC, HPC-8000), 0.5 parts by weight of 2-methylimidazole and 220 parts by weight of butanone were stirred uniformly to obtain a resin glue with a viscosity of 42 Pa·s;

[0120] S2: Add 50 parts by weight of boron nitride (made of Mizushima alloy, HP40-J2, D50=16.0 μm) to the above resin glue, continue to stir evenly, and obtain a resin glue with a viscosity of 281 Pa.s;

[0121] S3: Continue to add 70 parts by weight of calcium titanate (made by Kyoritsu Materials, D50=2.0 μm), and stir evenly to obtain a resin composition corresponding to Comparative Example 2;

[0122] The viscosity in steps S1, S2 and S3 is measured by a rotational viscometer at room temperature.

[0123] Comparative Example 3

[0124] A method for preparing a resin composition comprises the following steps:

[0125] S1: 40 parts by weight of bisphenol A cyanate prepolymer (produced by Tianqi), 60 parts by weight of biphenyl epoxy resin (NC3000 produced by Huayao), 20 parts by weight of dicyclopentadiene active ester (produced by DIC, HPC-8000), 0.5 parts by weight of 2-methylimidazole and 100 parts by weight of butanone were stirred uniformly to obtain a resin glue having a viscosity of 157 Pa·s;

[0126] S2: Add 50 parts by weight of silicon dioxide (produced by Lianrui, D50=3.0 μm) to the above resin glue, continue to stir evenly, and obtain a resin glue with a viscosity of 296 Pa.s;

[0127] S3: Continue to add 70 parts by weight of strontium titanate (produced by Sakai Chemical Industry, ST-03, D50=0.3 μm), and stir evenly to obtain a resin composition corresponding to Comparative Example 3;

[0128] The viscosity in steps S1, S2 and S3 is measured by a rotational viscometer at room temperature.

[0129] Comparative Example 4

[0130] A method for preparing a resin composition comprises the following steps:

[0131] S1: 40 parts by weight of bisphenol A cyanate prepolymer (produced by Tianqi), 60 parts by weight of biphenyl epoxy resin (NC3000 produced by Huayao), 20 parts by weight of dicyclopentadiene active ester (produced by DIC, HPC-8000), 0.5 parts by weight of 2-methylimidazole and 100 parts by weight of butanone were stirred uniformly to obtain a resin glue having a viscosity of 157 Pa·s;

[0132] S2: Add 70 parts by weight of boron nitride (made of Mizushima alloy, HP40-J2, D50=16.0 μm) to the above resin glue, continue to stir evenly, and obtain a resin glue with a viscosity of 320 Pa.s;

[0133] S3: Continue to add 50 parts by weight of silicon dioxide (produced by Lianrui, D50=2.0 μm), and stir evenly to obtain a resin composition corresponding to Comparative Example 4;

[0134] The viscosity in steps S1, S2 and S3 is measured by a rotational viscometer at room temperature.

[0135] E glass fiber cloth as reinforcement material 7628 After pretreatment with an epoxy silane coupling agent, the samples were immersed in the glue of the resin compositions obtained in Examples 1 to 4 and Comparative Examples 1 to 4, taken out after wetting, placed in a 155°C forced air drying oven, and baked for 3 to 6 minutes to obtain the semi-cured sheets corresponding to Examples 1 to 4 and Comparative Examples 1 to 4, respectively.

[0136] Copper-clad laminates corresponding to the above-mentioned embodiments 1 to 4 and comparative examples 1 to 4 were prepared. The method for preparing the copper-clad laminate was as follows: 4 semi-cured sheets prepared as above were cut to 300×300 mm, and the semi-cured sheets were stacked into a composite sheet with a certain stacking structure, and then a 35 μm thick electrolytic copper foil was placed on both sides of the composite sheet, and then placed in a vacuum hot press, and hot pressed for 1.5 h at a pressure of 1.5 MPa and a temperature of 220°C to obtain a copper-clad laminate.

[0137] The copper-clad laminates corresponding to the above-mentioned embodiments 1 to 4 and comparative examples 1 to 4 were used to perform performance tests. Specifically, the performance evaluation method is as follows:

[0138] (1) Glass transition temperature (Tg): Determined by differential scanning calorimetry (DSC) according to the DSC method specified in IPC-TM-650 2.4.24.4, with a heating rate of 10°C.

[0139] / min, frequency is 10Hz;

[0140] (2) Thermal conductivity: tested using ASTM D5470-2017 method;

[0141] (3) Dk and Df: Dielectric properties at 10 GHz measured according to IPC-TM-650 2.5.5.5, SPDR;

[0142] (4) Internal substrate quality: The internal substrate quality was observed under a microscope. If white spots and dried flowers appeared within an area of ​​300 mm × 300 mm, it was indicated as 0; if a few white spots and dried flowers appeared, it was indicated as Δ; if a large number of white spots and dried flowers appeared, it was indicated as ╳;

[0143] (5) Dispersion of fillers: Stir the glue solution evenly at room temperature and leave it for 24 hours to observe whether there is any sedimentation or coagulation.

[0144] The properties of the copper-clad laminates obtained using the prepregs in Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Table 3 below.

[0145] Table 3

[0146]

[0147]

[0148] The Example 1 and the Comparative Example 1 are compared in parallel. Compared with the Example 1, the viscosity of the resin glue obtained in the steps S1 and S2 in the Comparative Example 1 is higher, which causes the inorganic filler in the resin composition in the Comparative Example 1 to condense, affecting the base material quality of the copper-clad laminate. At the same time, the thermal conductivity, Dk value and glass strength of the copper-clad laminate in the Comparative Example 1 are lower than those of the copper-clad laminate in the Example 1. It can be seen that in the Example 1, by adjusting the viscosity of the resin glue in the steps S1 and S2, the nitrogen-based inorganic substances and the titanate-based inorganic substances can be well dispersed in the resin glue without condensation and sedimentation, thereby inhibiting the decrease of the Dk value of the resin composition, and obtaining a cured product with high thermal conductivity and high Dk value.

[0149] Example 2 and Comparative Example 2 are compared in parallel. Compared with Example 2, the viscosity of the resin glue obtained in step S1 in Comparative Example 2 is lower, resulting in the sedimentation of the boron nitride inorganic filler in the resin composition in Comparative Example 2, affecting the quality of the base material of the copper-clad laminate. It can be seen that in Example 2, by adjusting the viscosity of the resin glue in steps S1 and S2, the nitrogen-based inorganic substances can be well dispersed in the resin glue without sedimentation, thereby inhibiting the decrease in the Dk value of the resin composition, and obtaining a cured product with high thermal conductivity, high Dk value, and high performance.

[0150] Example 3 and Comparative Example 3 were compared in parallel. Compared with the high thermal conductivity inorganic filler silicon nitride added in Example 3, the common inorganic filler silicon dioxide was added in Comparative Example 3. The comparison shows that the copper-clad laminate in Example 3 has higher thermal conductivity, higher Dk value, and better substrate quality.

[0151] Example 1 and Comparative Example 4 were compared in parallel. Compared with the high Dk inorganic filler calcium titanate added in Example 1, the common inorganic filler silica was added in Comparative Example 4. The comparison shows that the copper-clad laminate in Example 1 has a higher Dk value.

[0152] It can be seen that in the preparation method of the resin composition of the present invention, on the one hand, by adjusting the order of adding the two inorganic fillers, the nitrogen inorganic filler is added first, and then the titanate inorganic filler is added, so that the two inorganic fillers with higher density can be well dispersed in the resin system, the dispersion performance of the inorganic filler is improved, and the decrease in thermal conductivity and Dk value is suppressed; on the other hand, by using a nitrogen inorganic with high thermal conductivity in combination with a titanate inorganic with high Dk (dielectric constant), the thermal conductivity and Dk value of the resin composition are further improved, and at the same time, the active ester and cyanate ester compounds are used to further reduce the dielectric loss and improve the heat resistance. On the basis of obtaining a resin composition that meets higher heat resistance and low dielectric loss, the thermal conductivity and high dielectric constant of the resin composition are improved, and good resin filler wettability is ensured, and a cured product with high heat resistance, high thermal conductivity, high dielectric constant and low dielectric loss is obtained, thereby obtaining a cured product with excellent comprehensive performance.

[0153] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0154] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a resin composition, characterized in that: The steps include: S1: 10-60 parts by weight of a cyanate compound, 10-80 parts by weight of an epoxy resin, 5-60 parts by weight of an active ester and 10-200 parts by weight of an organic solvent are stirred uniformly to obtain a resin glue solution; S2: first add 5-100 parts by weight of nitrogen-based inorganic substances or their dispersions into the resin glue and stir evenly; S3: adding 30-100 parts by weight of a titanate inorganic substance or a dispersion thereof, stirring evenly to obtain a resin composition; Wherein, the nitrogen inorganic substance is selected from at least one of aluminum nitride, boron nitride or silicon nitride; The titanate inorganic substance is selected from at least one of calcium titanate, strontium titanate, barium titanate, lead titanate, magnesium titanate, lead zirconate titanate, and lanthanum lead zirconate titanate.

2. The method for preparing the resin composition according to claim 1, wherein: The average particle size of the nitrogen-based inorganic material is 3-25 μm; the average particle size of the titanate-based inorganic material is 0.1-5 μm.

3. The method for preparing the resin composition according to claim 1, characterized in that: The viscosity of the resin glue obtained in step S1 at room temperature is 50-350 Pa·s.

4. The method for preparing the resin composition according to claim 1, wherein: The viscosity of the resin glue obtained in step S2 at room temperature is 200-600 Pa·s.

5. The method for preparing the resin composition according to claim 1, wherein: The organic solvent in the dispersion is of the same type as the organic solvent in step S1.

6. The method for preparing the resin composition according to claim 1, characterized in that: The active ester contains the following structure: Ar is C6-C 20 Arylene, Ar' is C1-C 20 An alkyl, aryl or alicyclic group.

7. The method for preparing the resin composition according to claim 6, characterized in that: Ar' is naphthyl, dicyclopentadienyl or Or -O-; wherein Ar is phenyl.

8. The method for preparing the resin composition according to claim 1, characterized in that: In step S1, 0.05-5 parts by weight of a curing accelerator is also added.

9. A resin composition, characterized in that: The resin composition is prepared by the method for preparing the resin composition according to any one of claims 1 to 8.

10. Use of the resin composition according to claim 9 in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.